Jim Dinsmore letter to Thomas Kent regarding field reports, June 22, 1993 - Dinsmore, James J.et al (1993)
Letter from Jim Dinsmore to Thomas Kent dated June 22, 1993. Dinsmore sends Kent field reports, and comments on some sightings, the printing and mailing schedule for Iowa Bird Life, and some bird specimens. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of Spring 1993. Plustek - flatbed